Contact angle testing method of composite geosynthetic material

The texture surface area of ​​composite geosynthetic materials and the proportion of hydrophilic/hydrophobic materials were determined by photocutting and image processing technology, and the apparent contact angle was calculated using the Cassie-Baxter and Wenzel models, which solved the problem of contact angle measurement of composite spinned geotextiles and achieved accurate and simple contact angle measurement.

CN120009129AInactive Publication Date: 2025-05-16HARBIN INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510502499.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-05-16
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to accurately measure the contact angle of composite spun geotextiles, especially materials with diverse chemical compositions, uneven surfaces and complex pore structures.

Method used

The texture surface area of ​​composite geosynthetic materials was determined by light-cutting method and the roughness factor was calculated; the surface area ratio of hydrophilic materials and hydrophobic materials was determined by combining image processing technology; the apparent contact angle was calculated by using the Cassie-Baxter model and the Wenzel model.

Benefits of technology

It realizes accurate measurement of the contact angle of composite spun geotextiles, which is characterized by simple operation, simple calculation and high repeatability, and can effectively characterize the wetting characteristics of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120009129A_ABST
    Figure CN120009129A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of geosynthetic material testing, and provides a method for testing a contact angle of a composite geosynthetic material. The method comprises the following steps: acquiring the composite geosynthetic material, measuring the texture surface area of the composite geosynthetic material by adopting a light-cutting method, and calculating a roughness factor of the composite geosynthetic material by utilizing the texture surface area; calculating the surface area ratio of the hydrophilic material to the hydrophobic material in the composite geosynthetic material; measuring the intrinsic contact angle of the hydrophilic material and the hydrophobic material in the composite geosynthetic material; the apparent contact angle of the composite geosynthetic material is calculated through a Cassie-Baxter model and a Wenzel model; the problems that in the prior art, a contact angle measuring method based on the Young's equation is not suitable for measuring the contact angle of the composite woven geotextile, and the contact angle of a composite material with various chemical components, an uneven surface and a complex pore structure cannot be accurately measured at present are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of geosynthetics testing, and relates to a contact angle testing method for composite geosynthetics. Background Art

[0002] Woven geotextiles are permeable synthetic materials made of synthetic fibers woven together. They have engineering properties such as high tensile strength, corrosion resistance, and good permeability. They play the role of reinforcement, isolation, protection, drainage, and filtration in geotechnical construction. The contact angle of geotextiles is an important indicator of the wettability of materials, and is also a reference for quantitative analysis of the penetration, hydrophilic / hydrophobic properties, and filtration properties of geotextiles.

[0003] With the continuous development of geosynthetics, a new type of geosynthetics with composite functions, namely composite woven geotextiles, has been formed, which are made of plastics (polyethylene, polyester, polypropylene, etc.) and fibers (basalt fiber, carbon fiber, glass fiber, etc.) as raw materials, through various combinations such as monofilament, multifilament and mixed yarn, and different weaving processes such as plain weave, twill and satin weave. They have wide applications and great development prospects in the fields of construction, transportation, disaster prevention, etc. However, the contact angle measurement method based on Young's equation is only applicable to ideal rigid, uniform, smooth and inert film materials, and is not suitable for the measurement of contact angles of composite woven geotextiles. How to accurately characterize the contact angle and wetting characteristics of composite materials with diverse chemical compositions, uneven surfaces and complex pore structures is the theoretical basis for realizing the penetration, isolation, anti-filtration and other functions of composite woven geotextiles, and is also one of the problems that need to be solved urgently in the field of geosynthetics. Summary of the invention

[0004] The purpose of the present invention is to provide a contact angle testing method for composite geosynthetics, which solves the problem that the contact angle measurement method based on Young's equation in the prior art is not suitable for measuring the contact angle of composite woven geotextiles, and the technical problem that the contact angle of composite materials with diverse chemical compositions, uneven surfaces and complex pore structures cannot be accurately measured.

[0005] The present invention provides a contact angle testing method for geosynthetics, comprising the following steps: Step S1: obtain a composite geosynthetics, determine the texture surface area of ​​the composite geosynthetics by light sectioning method, and calculate the roughness factor of the composite geosynthetics by using the texture surface area; Step S2: calculate the surface area ratio of the hydrophilic material and the hydrophobic material in the composite geosynthetics; Step S3: determine the intrinsic contact angle of the hydrophilic material and the hydrophobic material in the composite geosynthetics; Step S4: calculate the apparent contact angle of the composite geosynthetics by using the Cassie-Baxter model and the Wenzel model.

[0006] Further, step S1 is specifically as follows: step S11: obtaining composite geosynthetics, cutting the composite geosynthetics to obtain test materials, and fixing the test materials on a support pad; Step S12: Place the support pad covered with the test material under the semiconductor laser emitter, and use a laser texture scanner to scan the test material to obtain a surface texture model of the test material, and use the light section method to measure the surface texture model to obtain the texture surface area of ​​the test material. ; Step S13: Using the laser texture scanner to project the area on the surface of the test material Textured surface area of ​​the test material , calculate the roughness factor of geosynthetics , roughness factor The function expression is as follows: (1); in: is the projection area of ​​the laser texture scanner on the surface of the test material, is the texture surface area of ​​the test material, is the roughness factor of geosynthetics.

[0007] Furthermore, step S2 is specifically as follows: Step S21: Spread the test material flat on the table, and use a camera perpendicular to the table to take a picture of the test material; Step S22: using a median filter method to perform noise reduction processing on the test material image obtained in step S21 to obtain a noise-free test material image; Step S23: using a frequency domain method to enhance the noise-free test material image to obtain an enhanced noise-free test material image; Step S24: using an automatic threshold segmentation method to process the enhanced noise-free test material image to obtain a binary enhanced noise-free test material image; Step S25: input the binary enhanced noise-free test material image into Image J software, and use Image J software to calculate the surface area ratio of the hydrophilic material and the hydrophobic material in the composite geosynthetics.

[0008] Further, step S25 is specifically as follows: Step S251: Open the binary enhanced noise-free test material image in Image J software; Step S252: click the Image menu bar in the Image J software menu bar, select the Type option, and then select the 8-bit option in the Type option to obtain a test material image in 8-bit mode; Step S253: click the Analysis menu bar in the Image J software menu bar, select the Measurement Settings option, and in the Measurement Settings dialog box that pops up, select the Area option to analyze the area of ​​the test material image in 8-bit mode; Step S254: Click the Image menu bar of the Image J software menu bar, select the Adjustment option, and in the pop-up Threshold dialog box, drag the slider in the Threshold dialog box to adjust the threshold to obtain an image that can distinguish between the hydrophilic material and the hydrophobic material areas; Step S255: Image J software calculates the image that can distinguish the hydrophilic material and the hydrophobic material area to obtain the surface area ratio of the hydrophilic material in the composite geosynthetics and the surface area ratio of the hydrophobic material in the composite geosynthetics.

[0009] Furthermore, step S3 is specifically as follows: Step S31: cutting the test material into strip samples, the length of the strip samples ranges from 300 mm to 500 mm, disassembling the hydrophobic material in the strip samples into single filamentary hydrophobic fibers, and fixing the single filamentary hydrophobic fibers on the sample table using transparent tape; Step S32: turning on the contact angle measuring instrument, and adjusting the background light brightness and the sample table height so that the hydrophobic fibers on the sample table are clearly visible in the contact angle measuring instrument observation window; Step S33: inject distilled water into the micro-syringe, and adjust the position of the syringe through the observation window so that the tip of the micro-syringe is placed above the hydrophobic fiber, and a water drop is suspended on the tip of the micro-syringe; Step S34: Turn on the CCD industrial camera and set the camera shooting parameters; Step S35: raising the sample table so that the surface of the hydrophobic fiber contacts the water droplet suspended from the tip of the micro-injection syringe; Step S36: Calculate the intrinsic contact angle of the hydrophobic material in the geosynthetics using the width-height method.

[0010] Furthermore, step S4 is specifically as follows:

[0011] Step S41: Establishing the apparent contact angle of geosynthetics based on the Cassie-Baxter model Surface area ratio of hydrophobic materials The functional relationship expression is as follows: (2); in: is the apparent contact angle of geosynthetics, in degrees, is the surface area ratio of the hydrophobic material, is the apparent contact angle of the hydrophobic material of the geosynthetics, The apparent contact angle of the hydrophilic material of the geosynthetics; Step S42: Based on the intrinsic contact angle of the hydrophilic material , and the apparent contact angle of the geosynthetics is obtained Surface area ratio of hydrophobic material The functional relationship expression is as follows: (3); Step S43: Establishing the apparent contact angle of geosynthetics based on the Wenzel model Intrinsic contact angle with geosynthetics The function expression is as follows: (4); Step S44: Based on the functional expression of the apparent contact angle of the composite geosynthetics and the intrinsic contact angle of the composite geosynthetics, and the functional relationship expression between the apparent contact angle of the composite geosynthetics and the surface area ratio of the hydrophobic material, an expression for the apparent contact angle of the composite geosynthetics is established, as shown below: (5); in: It is the intrinsic contact angle of the hydrophobic material in the composite geosynthetics.

[0012] The camera shooting parameters are as follows: the camera exposure time is 1ms, the shooting frequency is 25 frames / second, and the shooting time is 20 seconds.

[0013] The beneficial effects of the present invention are: 1. The present invention proposes a contact angle test method for composite geosynthetics, which realizes the accurate measurement of the contact angle of composite woven geotextiles with diverse chemical compositions, uneven surfaces and complex pore structures, and has the characteristics of simple operation, simple calculation and high repeatability.

[0014] 2. With the continuous development of the field of geosynthetics, the raw materials, weaving processes and functions of geosynthetics have gradually developed from single to composite. However, the contact angle measurement method for composite woven geotextiles containing hydrophilic and hydrophobic materials is still blank. The present invention combines image processing technology to propose a method for determining the surface area ratio of hydrophilic and hydrophobic materials in composite woven geotextiles, which can simply and conveniently determine the ratio of each component of composite woven geosynthetics, and provide technical support for the measurement of contact angles of new geosynthetics with diverse chemical compositions and complex weaving structures in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 It is a flow chart of a contact angle test method for geosynthetics; Figure 2 It is a schematic diagram of the surface texture of geosynthetics drawn using the scanning results of a laser texture scanner; Figure 3 It is a schematic diagram of the system composition of the contact angle measuring instrument; Figure 4 It is a graph showing the change of apparent contact angle of geosynthetics over time.

[0017] The accompanying drawings are marked as follows: 1. industrial camera, 2. light source, 3. syringe fixture, 4. sample table. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] The present invention provides a contact angle test method for geosynthetics. Figure 1 As shown, the following steps are included: Step S1: obtaining a composite geosynthetics, measuring the texture surface area of ​​the composite geosynthetics by using a light section method, and calculating the roughness factor of the composite geosynthetics by using the texture surface area; Step S11: Select a flat, unbent composite geosynthetics material, cut the composite geosynthetics material into a square whose size does not exceed the maximum scanning size of the laser scanner as a test material, and affix double-sided tape to the back edge and diagonal of the test material, and lay the sample flat and fix it on the support pad; In this embodiment, the specific steps are as follows: a flat, unbent composite geosynthetics is selected, and the composite geosynthetics is cut into square test materials with a size of 30 cm × 30 cm, and double-sided tape is attached to the back edge and diagonal of the test material so that the sample can be laid flat and fixed on the support pad to ensure that the test material has no warping, wrinkles, etc.; Step S12: placing the support plate covered with the test material at the lower end of the semiconductor laser emitter, and using the laser texture scanner on the semiconductor laser emitter to scan the test material to obtain a surface texture model of the test material, and using the light section method to measure the surface texture model to obtain the texture surface area of ​​the test material ; Specifically in this embodiment: a support plate covered with the test material is placed at the lower end of the semiconductor laser emitter to ensure that the strip-shaped purple laser of the laser scanner is perpendicular to the support plate to prevent the laser beam from being offset during the scanning process. In this embodiment, the texture measurement accuracy of the xy plane corresponding to the laser scanner is 0.01mm, and the texture measurement accuracy in the z direction is 0.005mm. The scanning speed is 6.4m / s, and the full range scan can be completed within 1 minute, and the scanning range is 100mm×100mm. During the scanning process of the laser scanner, the laser beam is magnified into a strip-shaped purple laser line through the cylinder, and diffusely reflected after passing through the test material. The reflected light is filtered by the objective lens and received by the photoelectric element. The distance from different laser beams to the test material is calculated by measuring the time from the emission to the reception of the laser beam, and then the texture profile of the surface of the test material is obtained, and the texture surface area of ​​the test material is calculated.

[0020] The working principle of laser texture scanner: the laser beam is emitted through the semiconductor laser emitter, and the laser beam is expanded into a strip laser line by the cylindrical objective lens. The curve image obtained by the intersection of the light band and the surface contour of the material is the micro-geometry of the surface. The reflected light is filtered by the filter and received by the photoelectric element. The distance from different laser beams to the test material is calculated by measuring the time from the emission to the reception of the laser beam. Then, the spatial relative coordinates of each scanning point and the measuring station can be obtained by combining the horizontal and vertical angles of each scanning point, and then the texture contour of the test material surface can be obtained, and the texture surface area of ​​the test material can be further calculated. ; The operating frequency of the semiconductor laser transmitter is 1kHz, the maximum contour accuracy is 0.01mm, the elevation accuracy is 0.004mm, and the minimum scanning area is 30mm×30mm. The texture of the surface of the composite geosynthetics drawn according to the scanning results is as follows Figure 2 shown.

[0021] Step S13: Using the laser texture scanner to project the area on the surface of the test material Textured surface area of ​​the test material Calculating the roughness factor of geosynthetics , roughness factor The function expression is as follows: (1);

[0022] Step S2: Calculate the surface area ratio of the hydrophilic material and the hydrophobic material of the geosynthetics using Image J software; Step S21: Select a flat geosynthetic composite material, cut the geosynthetic composite material into a square whose size does not exceed the maximum scanning size of the laser scanner as a test material, spread the test material on a flat and smooth table, and use a camera perpendicular to the table surface to take a picture of the test material; Step S22: Using the median filtering method to perform noise reduction processing on the test material image obtained in step S21 to obtain a noise-free test material image.

[0023] The principle of noise reduction is: replace the gray value of the pixel point of the test material image with the median of the gray values ​​of all pixels in the neighborhood of the point, thereby eliminating the noise points in the image; Step S23: using a frequency domain method to enhance the noise-free test material image to obtain an enhanced noise-free test material image; The principle of enhancement processing is to regard the digital image after noise reduction as a two-dimensional signal and perform Fourier transform on it to enhance the contrast and clarity of different material compositions in the image.

[0024] Step S24: using an automatic threshold segmentation method to process the enhanced noise-free test material image to obtain a binary enhanced noise-free test material image; Step S25: input the binary enhanced noise-free test material image into Image J software, and use Image J software to calculate the surface area ratio of the hydrophilic material and the hydrophobic material in the composite geosynthetics.

[0025] Image J is a public image processing software based on Java.

[0026] Step S251: Open the binary enhanced noise-free test material image in Image J software; Step S252: click the Image menu bar in the Image J software menu bar, select the Type option, and then select the 8-bit option in the Type option to obtain a test material image in 8-bit mode; Step S253: click the Analysis menu bar in the Image J software menu bar, select the Measurement Settings option, and in the Measurement Settings dialog box that pops up, select the Area option to analyze the area of ​​the test material image in 8-bit mode; Step S254: Click the Image menu bar of the Image J software menu bar, select the Adjustment option, and in the Threshold dialog box that pops up, drag the slider in the Threshold dialog box to adjust the threshold to obtain an image that can clearly distinguish the hydrophilic material area from the hydrophobic material area; The principle is: since there is an obvious difference in the grayscale values ​​of hydrophilic materials (white) and hydrophobic materials (black) in the calculation object, the threshold is adjusted by dragging the slider to distinguish the grayscale value boundary in the calculation object area. The area with a grayscale value greater than the threshold is set as hydrophilic material, and the area with a grayscale value less than the threshold is set as hydrophobic material.

[0027] Step S255: Image J software calculates the image that clearly distinguishes the hydrophilic material area from the hydrophobic material area to obtain the surface area ratio of the hydrophilic material in the composite geosynthetics and the surface area ratio of the hydrophobic material in the composite geosynthetics.

[0028] The proportion of hydrophilic material in the test material of this embodiment is 0.19, the proportion of hydrophobic materials It is 0.81.

[0029] Step S3: measuring the intrinsic contact angles of the hydrophilic material and the hydrophobic material of the composite geosynthetics; Step S31: cutting the test material into strip samples, the length of the strip samples ranges from 300 mm to 500 mm, disassembling the hydrophilic material in the strip samples into single filamentary hydrophilic fibers, and fixing the single filamentary hydrophilic fibers on the sample table with transparent tape, ensuring that the hydrophilic fibers and the hydrophobic fibers are parallel and closely attached to the sample table; Step S32: Open Figure 3 The contact angle measuring instrument shown is used to adjust the background light brightness, the height of the sample stage and the front-to-back distance so that the fibers in the observation window are clearly visible; Step S33: inject distilled water into the micro-syringe so that the volume of the water drop hanging at the end of the micro-syringe needle is 2 μL ± 0.5 ml, and adjust the position of the syringe through the observation window so that the tip of the micro-syringe needle is placed 3-5 mm above the test material; Step S34: Turn on the CCD industrial camera and set the camera shooting parameters; Step S35: raising the sample stage to make the fiber surface contact the water droplet hanging from the end of the micro-syringe needle, removing the sample to obtain a state where the water droplet has completed the transfer, and then lowering the sample stage to obtain a result where the needle end is separated from the water droplet; Step S36: Calculate the intrinsic contact angle of the hydrophobic material of the geosynthetics using the width-height method.

[0030] The test methods for the contact angle of hydrophobic materials and hydrophilic materials of geosynthetics are the same.

[0031] The contact angles of the hydrophilic material and the hydrophobic material of the test material of this embodiment are 0° and 180°.

[0032] Figure 3The structure of the contact angle meter is as follows: the contact angle meter is composed of a light source 2, an industrial camera 1, a sample table 4 and a liquid supply system, wherein the liquid supply system includes a syringe clamp 3 and a manual micro-injector, the light source 2 can be a halogen lamp, an incandescent lamp or a light-type lamp, the heat generated by which cannot affect the test material or water droplets, the exposure time of the industrial camera 1 is 1ms, the shooting frequency can reach 25 photos per minute, and the sample table 4 ensures that the sample can be placed flat and horizontally.

[0033] Step S4: Calculating the apparent contact angle of the geosynthetics using the Cassie-Baxter model and the Wenzel model;

[0034] Step S41: Establishing the apparent contact angle of the composite material based on the Cassie-Baxter model Surface area ratio of hydrophobic materials The functional relationship expression is as follows: (2); in: is the apparent contact angle of geosynthetics, in degrees, is the surface area ratio of the hydrophobic material, is the apparent contact angle of the hydrophobic material of the geosynthetics, The apparent contact angle of the hydrophilic material of the geosynthetics; Step S42: Based on the intrinsic contact angle of the hydrophilic material , established as the apparent contact angle of geosynthetics Surface area ratio of hydrophobic materials The functional relationship expression is as follows: (3); In this embodiment, the intrinsic contact angle of the hydrophilic material is , Reason: When the S31-S36 method was used to test the intrinsic contact angle of hydrophilic materials, it was found that the droplets quickly entered the pores of the hydrophilic materials. Based on this, the intrinsic contact angle of the hydrophilic materials .

[0035] Step S43: Based on the Wenzel model, a functional expression of the apparent contact angle of the composite geosynthetics and the intrinsic contact angle of the composite geosynthetics is established as follows: (4); Step S44: Based on the functional expression of the apparent contact angle of the composite geosynthetics and the intrinsic contact angle of the composite geosynthetics, and the functional relationship expression between the apparent contact angle of the composite geosynthetics and the surface area ratio of the hydrophobic material of the composite geosynthetics, an expression for the apparent contact angle of the composite geosynthetics is established, as shown below: (5); in: It is the intrinsic contact angle of the hydrophobic material in the composite geosynthetics.

[0036] The camera exposure time is 1ms, the shooting frequency is 25 frames / second, and the shooting time is 20 seconds.

[0037] The apparent contact angle of the composite geosynthetics used in the test of this embodiment is calculated using formula (5) to be 101°.

[0038] The present invention fully considers the influence of the surface roughness of woven geotextiles on the contact angle measurement, uses laser testing technology to measure the actual contact area of ​​the composite geotextile, and determines the roughness factor of the material. Secondly, in view of the characteristics of composite geotextiles that are both hydrophilic and hydrophobic materials, the surface area ratio of hydrophilic materials and hydrophobic materials in the composite geotextile is determined in combination with image processing technology, and the influence of material properties on the contact angle measurement is quantitatively characterized. Thirdly, an optical measuring instrument is used to measure the contact angles of hydrophilic fibers and hydrophobic fibers respectively. Finally, based on the Cassie-Baxter theoretical model, the contact angle of the hydrophilic-hydrophobic composite geosynthetics is calculated by considering the surface roughness and material properties of the composite material.

[0039] Figure 4 The graph showing the change of the apparent contact angle of the composite geosynthetics calculated by the method proposed in this application over time is shown in FIG. Figure 4 It can be seen that the apparent contact angle of the composite geosynthetics is 97.2° at 0 seconds, and the apparent contact angle decreases rapidly with the increase of test time. The apparent contact angle of the composite geosynthetics is 20.1° at 1 second, and the apparent contact angle of the composite geosynthetics is 9° at 1.3 seconds.

[0040] The calculation method proposed in the present invention avoids the large human errors caused by direct measurement. By measuring the intrinsic contact angle, surface roughness and area ratio of different components of the material, the characterization contact angle of the composite geosynthetics can be calculated effectively and quickly, solving the limitations of the traditional contact angle measurement method in measuring the contact angle of composite woven geotextiles, such as large discreteness of data results and great influence of human factors.

[0041] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A method for testing the contact angle of geosynthetics, characterized in that: Follow these steps: Step S1: obtaining a composite geosynthetics, measuring the texture surface area of ​​the composite geosynthetics by using a light section method, and calculating the roughness factor of the composite geosynthetics by using the texture surface area; Step S2: Calculate the surface area ratio of the hydrophilic material and the hydrophobic material in the composite geosynthetics; Step S3: measuring the intrinsic contact angles of the hydrophilic material and the hydrophobic material in the composite geosynthetics; Step S4: Calculate the apparent contact angle of the geosynthetics using the Cassie-Baxter model and the Wenzel model.

2. A contact angle testing method for composite geosynthetics according to claim 1, characterized in that: The specific operations of step S1 are as follows: Step S11: obtaining a composite geosynthetics material, cutting the composite geosynthetics material to obtain a test material, and fixing the test material on a support pad; Step S12: Place the support pad with the test material under the semiconductor laser emitter, and use a laser texture scanner to scan the test material to obtain a surface texture model of the test material. Use the light section method to measure the surface texture model to obtain the texture surface area of ​​the test material. ; Step S13: Using the laser texture scanner to project the area on the surface of the test material Textured surface area of ​​the test material , calculate the roughness factor of geosynthetics , roughness factor The function expression is as follows: (1); in: is the projection area of ​​the laser texture scanner on the surface of the test material, is the texture surface area of ​​the test material, is the roughness factor of geosynthetics.

3. The contact angle test method of a composite geosynthetics according to claim 1, characterized in that: The specific operations of step S2 are as follows: Step S21: Spread the test material flat on the table, and use a camera perpendicular to the table to take a picture of the test material; Step S22: using a median filter method to perform noise reduction processing on the test material image obtained in step S21 to obtain a noise-free test material image; Step S23: using a frequency domain method to enhance the noise-free test material image to obtain an enhanced noise-free test material image; Step S24: using an automatic threshold segmentation method to process the enhanced noise-free test material image to obtain a binary enhanced noise-free test material image; Step S25: input the binary enhanced noise-free test material image into Image J software, and use Image J software to calculate the surface area ratio of the hydrophilic material and the hydrophobic material in the composite geosynthetics.

4. A contact angle testing method for composite geosynthetics according to claim 3, characterized in that: The specific operation of step S25 is as follows: Step S251: Open the binary enhanced noise-free test material image in Image J software; Step S252: click the Image menu bar in the Image J software menu bar, select the Type option, and then select the 8-bit option in the Type option to obtain a test material image in 8-bit mode; Step S253: click the Analysis menu bar in the Image J software menu bar, select the Measurement Settings option, and in the Measurement Settings dialog box that pops up, select the Area option to analyze the area of ​​the test material image in 8-bit mode; Step S254: Click the Image menu bar of the Image J software menu bar, select the Adjustment option, and in the pop-up Threshold dialog box, drag the slider in the Threshold dialog box to adjust the threshold to obtain an image that can distinguish between the hydrophilic material and the hydrophobic material areas; Step S255: Image J software calculates the image that can distinguish the hydrophilic material and the hydrophobic material area to obtain the surface area ratio of the hydrophilic material in the composite geosynthetics and the surface area ratio of the hydrophobic material in the composite geosynthetics.

5. The contact angle test method of geosynthetics according to claim 1, characterized in that: The specific method for testing the intrinsic contact angle of the hydrophobic material of the composite geosynthetics in step S3 is as follows: Step S31: cutting the test material into strip samples, the length of the strip samples ranges from 300 mm to 500 mm, disassembling the hydrophobic material in the strip samples into single filamentary hydrophobic fibers, and fixing the single filamentary hydrophobic fibers on the sample table using transparent tape; Step S32: turning on the contact angle measuring instrument, and adjusting the background light brightness and the sample table height so that the hydrophobic fibers on the sample table are clearly visible in the contact angle measuring instrument observation window; Step S33: inject distilled water into the micro-syringe, and adjust the position of the syringe through the observation window so that the tip of the micro-syringe is placed above the hydrophobic fiber, and a water drop is suspended on the tip of the micro-syringe; Step S34: Turn on the CCD industrial camera and set the camera shooting parameters; Step S35: raising the sample table so that the surface of the hydrophobic fiber contacts the water droplet suspended from the tip of the micro-injection syringe; Step S36: Calculate the intrinsic contact angle of the hydrophobic material in the geosynthetics using the width-height method.

6. The contact angle test method of geosynthetics according to claim 1, characterized in that: The specific operations of step S4 are as follows: Step S41: Establishing the apparent contact angle of geosynthetics based on the Cassie-Baxter model Surface area ratio of hydrophobic materials The functional relationship expression is as follows: (2); in: is the apparent contact angle of geosynthetics, in degrees, is the surface area ratio of the hydrophobic material, is the apparent contact angle of the hydrophobic material of the geosynthetics, The apparent contact angle of the hydrophilic material of the geosynthetics; Step S42: Based on the intrinsic contact angle of the hydrophilic material , and the apparent contact angle of the geosynthetics is obtained Surface area ratio of hydrophobic materials The functional relationship expression is as follows: (3); Step S43: Establishing the apparent contact angle of geosynthetics based on the Wenzel model Intrinsic contact angle with geosynthetics The function expression is as follows: (4); Step S44: Based on the functional expression of the apparent contact angle of the composite geosynthetics and the intrinsic contact angle of the composite geosynthetics, and the functional relationship expression between the apparent contact angle of the composite geosynthetics and the surface area ratio of the hydrophobic material, an expression for the apparent contact angle of the composite geosynthetics is established, as shown below: (5); in: It is the intrinsic contact angle of the hydrophobic material in the composite geosynthetics.

7. The contact angle test method of geosynthetics according to claim 5, characterized in that: The camera shooting parameters are as follows: the camera exposure time is 1ms, the shooting frequency is 25 frames / second, and the shooting time is 20 seconds.

Citation Information

Patent Citations

  • Method for evaluating fracturing property of shale based on rock debris microscopic characteristics

    CN105445440A

  • Preparation of hydrophobic coating and evaluation method for hydrophobicity

    CN105486610A

  • Device and method for testing wettability of hydrophilic porous material

    CN107764698A